A new approach for detection of wear mechanisms and determination of tool life in turning using acoustic emission. (December 2015) - Maia, Luis Henrique Andrade; Abrao, Alexandre Mendes; Vasconcelos, Wander Luiz; Sales, Wisley Falco; Machado, Alisson Rocha
Abstract: A methodology for detection of wear mechanisms and determination of end of life of the cutting tool based on the acoustic emission signals is proposed, using an innovative technique. With this technique, the AE signals generated in hardened AISI 4340 steel turning respond well to the tool wear evolution. The tests were made using common and nanostructured AlCrN coated and uncoated cemented carbide tools. The AE signal spectrum is correlated with the wear mechanisms identified in the cutting tools and compared to the excitation frequency values corresponding to the respective mechanisms validating the identification of the wear mechanisms. The evolution of maximum flank wear resulted in increasing amplitude of average of Power Spectral Density at the end of life. Highlights: A new methodology was developed for better treatment of AE signals from the wear. The acoustic emission signals amplitude increased with tool wear life. The tools PSD signals without coating respond differently of the coated tools. The frequencies found in AE signals correspond to tool wear mechanisms of tools.